Некоторые замечания о сходимости численно-аналитического метода последовательных приближений - Ронто, М.; Месарош, Й. (Український математичний журнал, 1996)
We establish new improved estimates necessary for the justification of the numerical-analytic method for the investigation of the existence and construction of approximate solutions of nonlinear boundary-value problems for ordinary differential equations.